Empirical examination of economic linkages between Japan and rest of Asia. - Lim, Kok Soon. (2008)
The overall objective of our paper is to use econometric analysis to empirically examine whether the Japanese economy does, in fact, have strong effects on other East Asian economies. Our results indicate that although Japanese economic performance does affect the performance of the region’s economies, the effects are weaker than might be expected. Therefore, our study finds at most only limited empirical support for the Japan-as-an-engine-of-growth theory.